Impact of previous hepatitis B infection on the clinical outcomes from chronic hepatitis C? A population‐level analysis. Issue 8 (15th April 2018) - Wang, H.; Swann, R.; Thomas, E.; Innes, H. A.; Valerio, H.; Hayes, P. C.; Allen, S.; Barclay, S. T.; Wilks, D.; Fox, R.; Bhattacharyya, D.; Kennedy, N.; et al.
Summary: Chronic coinfection with hepatitis C virus (HCV) and hepatitis B virus (HBV) is associated with adverse liver outcomes. The clinical impact of previous HBV infection on liver disease in HCV infection is unknown. We aimed at determining any association of previous HBV infection with liver outcomes using antibodies to the hepatitis B core antigen (HBcAb) positivity as a marker of exposure. The Scottish Hepatitis C Clinical Database containing data for all patients attending HCV clinics in participating health boards was linked to the HBV diagnostic registry and mortality data from Information Services Division, Scotland. Survival analyses with competing risks were constructed for time from the first appointment to decompensated cirrhosis, hepatocellular carcinoma (HCC) and liver‐related mortality. Records of 8513 chronic HCV patients were included in the analyses (87 HBcAb positive and HBV surface antigen [HBsAg] positive, 1577 HBcAb positive and HBsAg negative, and 6849 HBcAb negative). Multivariate cause‐specific proportional hazards models showed previous HBV infection (HBcAb positive and HBsAg negative) significantly increased the risks of decompensated cirrhosis (hazard ratio [HR]: 1.29, 95% CI: 1.01‐1.65) and HCC (HR: 1.64, 95% CI: 1.09‐2.49), but not liver‐related death (HR: 1.02, 95% CI: 0.80‐1.30). This is the largest study to date showing an association between previous HBV infection and certain adverse liver outcomes in HCV infection. Our analyses add significantly to evidence which suggests that HBV infection adversely affects liver health despite apparent clearance. This has important implications for HBV vaccination policy and indications for prioritization of HCV therapy.